Recruitment of RAG1 and RAG2 to Chromatinized DNA during V(D)J Recombination - Shetty, Keerthi (Mol Cell Biol, 2015)
V(D)J recombination is initiated by the binding of the RAG1 and RAG2 proteins to recombination signal sequences (RSSs) that consist of conserved heptamer and nonamer sequences separated by a spacer of either 12 or 23 bp. Here, we used RAG-inducible pro-B v-Abl cell lines in conjunction with chromatin immunoprecipitation to better understand the protein and RSS requirements for RAG recruitment to chromatin. Using a catalytic mutant form of RAG1 to prevent recombination, we did not observe cooperation between RAG1 and RAG2 in their recruitment to endogenous Jκ gene segments over a 48-h time course. Using retroviral recombination substrates, we found that RAG1 was recruited inefficiently to substrates lacking an RSS or containing a single RSS, better to substrates with two 12-bp RSSs (12RSSs) or two 23-bp RSSs (23RSSs), and more efficiently to a substrate with a 12/23RSS pair. RSS mutagenesis demonstrated a major role for the nonamer element in RAG1 binding, and correspondingly, a cryptic RSS consisting of a repeat of CA dinucleotides, which poorly re-creates the nonamer, was ineffective in recruiting RAG1. Our findings suggest that 12RSS-23RSS cooperation (the “12/23 rule”) is important not only for regulating RAG-mediated DNA cleavage but also for the efficiency of RAG recruitment to chromatin.